Exploring the effectiveness of online learning tools and technologies while teaching Maritime English to future ship engineers - Olena S. Diahyleva; Alona Yu. Yurzhenko; Olena Yu. Kononova (Academy of Cognitive and Natural Sciences, 2024)
Maritime English proficiency is crucial for future ship engineers to effectively communicate, operate, and ensure safety in the globalised marine industry. The study is devoted to analysing the integration of language and technical skills, highlighting their symbiotic relationship in the educational context. This paper explores the development of modern approaches to teaching Maritime English, emphasising continuous assessment and adapting teaching strategies. The assessment and evaluation methods were used to measure language proficiency, demonstrating the importance of ongoing assessment to monitor progress and adapt teaching strategies. Additionally, this article examines the influence of e-learning and digital resources, shedding light on advancements, challenges, and opportunities in Maritime English education. The importance of cross-cultural communication training is discussed, emphasising its role in preparing future ship engineers for an international working environment on a ship. Case studies, best practices, and lessons conducted at Kherson State Maritime Academy (KSMA), Ukraine, are shared to provide practical insights for teachers. The implications of international language proficiency regulations in the maritime industry are also addressed. By analysing the impact of these pedagogical approaches on ship engineers' safety and crisis management capabilities, this article highlights the tangible benefits of effective Maritime English education. For mobile learning app developers, the study suggests integrating features that promote collaborative learning, interactive assessments, and personalised feedback to optimise learning experiences. Overall, integrating online learning tools and technologies (e.g. Moodle LMS) presents a promising avenue for advancing Maritime English education and preparing future ship engineers for the challenges of the marine industry today.